PERANCANGAN ULANG USER INTERFACE PADA APLIKASI JUST MEME MENGGUNAKAN METODE DESIGN THINKING - Gozalianto, Rafli Gozalianto; Himala Praptami Adys; Baizul Zaman (STMIK KHARISMA Makassar, 2024)
This study aims to modify the user interface (UI) of the Just Meme application by applying the design thinking approach to achieve a better UI. Data collection was conducted by distributing questionnaires to 21 respondents using Google Form. The collected data was then processed using the System Usability Scale (SUS) method. The initial UI testing with the SUS method resulted in a score of